Beautiful chaos ebook - Garcia, Kami (Beautiful Creatures, 2011)
The third book in the New York Times bestselling series, perfect for fans of Cassandra Clare and Maggie Stiefvater! Ethan Wate thought he was getting used to the strange, impossible events happening in Gatlin, his small Southern town. But now that Ethan and Lena have returned home from the Great Barrier, strange and impossible have taken on new meanings. Swarms of locusts, record-breaking heat, and devastating storms ravage Gatlin as Ethan and Lena struggle to understand the impact of Lena's Claiming. Even Lena's family of powerful Supernaturals is affected — and their abilities begin to dangerously misfire. As time passes, one question becomes clear: What — or who — will need to be sacrificed to save Gatlin? For Ethan, the chaos is a frightening but welcome distraction. He's being haunted in his dreams again, but this time it's not Lena — and the mysterious figure is following him out of his dreams and into his everyday life. Worse, Ethan is gradually losing pieces of himself — forgetting names, phone numbers, even memories. He doesn't know why, and he's afraid to ask. Sometimes there's no going back. And this time there won't be a happy ending.